2019
DOI: 10.1038/s41590-019-0480-4
|View full text |Cite
|
Sign up to set email alerts
|

PTPN2 regulates the generation of exhausted CD8+ T cell subpopulations and restrains tumor immunity

Abstract: CD8 + T cell exhaustion is a state of dysfunction acquired in chronic viral infection and cancer, characterized by the formation of Slamf6 + progenitor exhausted and Tim-3 + terminally exhausted subpopulations through unknown mechanisms. Here we establish the phosphatase PTPN2 as a novel regulator of the differentiation of the terminally exhausted subpopulation that functions by Users may view, print, copy, and download text and data-mine the content in such documents, for the purposes of academic research, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
170
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(188 citation statements)
references
References 59 publications
18
170
0
Order By: Relevance
“…Similarly, TCF1 (mouse homolog of hTCF7) is also known as a driver of pre-exhausted CD8 progenitor population in chronic viral infection (36). The CD8_e2 subset also expressed intermediate levels of PDCD1 and higher SLAMF6, consistent with the phenotype of progenitor population of exhausted T cells as described in the literature (37,38). In addition, our ssGSEA analysis found that effector and central/resident memory sub-clusters exhibit different levels of genes contributing to signatures for CD8 activation inflammatory-pathway related genes for IL2/Stat5, IL6-Jak/Stat, TNFa via NFkB, Type II (IFNg) interferon signaling and anti-inflammatory signaling ( Fig S2E).…”
Section: Cd8 + T Cells Exhibit Continuum Of Distinct Transcriptional supporting
confidence: 58%
“…Similarly, TCF1 (mouse homolog of hTCF7) is also known as a driver of pre-exhausted CD8 progenitor population in chronic viral infection (36). The CD8_e2 subset also expressed intermediate levels of PDCD1 and higher SLAMF6, consistent with the phenotype of progenitor population of exhausted T cells as described in the literature (37,38). In addition, our ssGSEA analysis found that effector and central/resident memory sub-clusters exhibit different levels of genes contributing to signatures for CD8 activation inflammatory-pathway related genes for IL2/Stat5, IL6-Jak/Stat, TNFa via NFkB, Type II (IFNg) interferon signaling and anti-inflammatory signaling ( Fig S2E).…”
Section: Cd8 + T Cells Exhibit Continuum Of Distinct Transcriptional supporting
confidence: 58%
“…In order to construct a reference atlas for LCMV infection, we collected scRNA-seq data of virus-specific CD8 T (P14) cells in five batches from three different studies [39][40][41] , consisting of single-cell gene expression measurements at different time points for acute and chronic LCMV infection ( Figure 4A). Alignment by STACAS ( Figure 4B) was followed by unsupervised clustering (Figure 4C With this reference LCMV map in hand, we proceeded to project new datasets onto the atlas to study the effect of genetic alterations on CD8 T cells during viral infection.…”
Section: Custom Reference Atlases: the Transcriptomic Landscape Of T mentioning
confidence: 99%
“…4c ; Human: Extended Data Fig. 5d and 5h ), the latter of which has been shown to repress Tcf1 activity and inhibit the formation of progenitor exhausted CD8 + T cells 5,6 . We validated our scRNA-seq analyses with FACS-sorted CD8 + TILs at different stages of differentiation.…”
Section: Cd8+ T Cell Immunity Is Required For Sex Differences In Murimentioning
confidence: 99%
“…Human cancers show an analogous male-biased frequency of exhausted CD8 + T cells. Mechanistically, we describe an opposing interplay between CD8 + T cell intrinsic androgen and type I interferon 5,6 signaling in Tcf1/ Tcf7 regulation and formation of the progenitor exhausted T cell subset. Consistent with female-biased interferon response 7 , testosterone-dependent stimulation of Tcf1/ Tcf7 and resistance to interferon occurs to a greater magnitude in male CD8 + T cells.…”
mentioning
confidence: 99%